Ca-doped ZrO2 loaded Co-Mo electrocatalyst as well as preparation method and application thereof
By doping Ca on the ZrO2 support and introducing Co-Mo bimetal oxide, a Ca-doped ZrO2 supported Co-Mo electrocatalyst was prepared, which solved the problem of unsatisfactory NRR selectivity in the existing technology and achieved efficient nitrogen Directed conversion and highly selective ammonia production.
Patent Information
- Application Number
- CN202411470900.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to develop highly active electrocatalytic electrocatalytic nitrogen reduction (NRR) and inhibit hydrogen evolution side reaction (HER), resulting in unsatisfactory selectivity for directional nitrogen conversion.
Use water heat synthesis and roasting methods to prepare the CA doped ZRO2 load CO-MO electrocatalyst. By introducing CO to form CO-MO dual-metal oxides, and introduce a two-price CA2+to ZRO2, regulate the electronic structure, enhance nitrogen adsorption and activated performance performance Essence
It significantly improves the selectivity and activity of catalytic ammonia production, reduces the occurrence of side reactions of moisture desorption and hydrogen, and achieves efficient directional conversion of nitrogen.
Smart Images

Figure CN119352082A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalytic nitrogen reduction ammonia synthesis, and in particular to a highly active electrocatalyst capable of promoting electrocatalytic nitrogen reduction (NRR) while inhibiting hydrogen evolution side reaction (HER) and a preparation method thereof. Background Art
[0002] Electrocatalytic nitrogen reduction (NRR) nitrogen fixation can use nitrogen and water to synthesize ammonia (N2+3H2O→2NH3+3 / 2O2). The electrocatalytic system consists of a cathode nitrogen reduction reaction (NRR, N2+6H + +6e - →2NH3) and anodic oxygen evolution reaction (OER, 3H2O→3 / 2O2+6H + +6e - ), while NRR usually occurs at the cathode with the side reaction of hydrogen evolution (HER, 2H2O+2e - →H2+2OH - ).
[0003] Thermodynamically, NRR and HER occur at similar potentials. The hydrogenation process of electrocatalytic NRR to generate NH3 using water as the hydrogen source requires the transfer of 6 electrons, while the HER process only requires the transfer of 2 electrons. In terms of kinetics, NRR is very slow. The kinetic difference between NRR and HER makes the competition between the two complicated. The NRR process is often hindered by HER, resulting in low selectivity and poor activity. To this end, various electrocatalysts have been developed in the prior art, and a variety of control strategies have been adopted to control NRR and HER, but HER still dominates. For example, the invention patent with application number 2024113634333 discloses an electrocatalyst, and the specific preparation method is to embed MoS2 and ZrS3 nanocrystals on a ZrO2 nanosheet carrier to form a heterojunction to obtain a MoS2-ZrS3 / ZrO2 electrocatalyst, which shows good catalytic performance, but MoS2 is also an ideal catalyst for hydrogen production by electrolysis of water, and has a high HER catalytic activity, resulting in the unsatisfactory selectivity of the ammonia production of the MoS2-ZrS3 / ZrO2 electrocatalyst, and there is still a lot of room for improvement.
[0004] Therefore, developing highly active electrocatalysts that can promote NRR while suppressing HER and achieve highly selective nitrogen directional conversion has always been a major challenge hindering the development of this field. Summary of the invention
[0005] In view of this, the present disclosure provides a Ca-doped ZrO2-loaded Co-Mo electrocatalyst to solve the problem that the current high-activity electrocatalysts that can promote NRR and inhibit HER at the same time still have unsatisfactory selectivity.
[0006] The technical concept of the preparation method of the Ca-doped ZrO2-loaded Co-Mo electrocatalyst of the present invention is:
[0007] The electrocatalyst was prepared by a two-step hydrothermal synthesis and calcination method. Co was introduced to form a Co-Mo bimetallic oxide, which synergistically promoted the electrocatalytic activity. At the same time, divalent Ca was introduced into the matrix ZrO2. 2+ , regulating the electronic structure of ZrO2 and its loaded Mo component, regulating the adsorption and activation performance of the electrocatalyst for N2, and at the same time, the divalent Ca 2+ Doped into the ZrO2 lattice, partially replacing tetravalent Zr 4+ In order to maintain local electrical neutrality, the oxygen vacancies on the ZrO2 surface are increased, which is conducive to loosening and activating the N≡N triple bond, further improving the electrocatalytic ammonia production performance of the catalyst.
[0008] To achieve the above-mentioned object of the invention, in a first aspect, the preparation method of the Ca-doped ZrO2-loaded Co-Mo electrocatalyst comprises:
[0009] Hydrothermally synthesizing cobalt salt, calcium salt, zirconium salt and molybdate to prepare electrocatalyst precursor;
[0010] The electrocatalyst precursor is calcined to obtain the Ca-doped ZrO2-loaded Co-Mo electrocatalyst.
[0011] In the present disclosure and possible embodiments, the cobalt salt includes cobalt chloride, cobalt sulfate and cobalt nitrate;
[0012] The calcium salts include calcium chloride and calcium nitrate;
[0013] The molybdate includes sodium molybdate and ammonium molybdate;
[0014] The zirconium salts include zirconium oxychloride, zirconium chloride and zirconium nitrate.
[0015] In the present disclosure and possible embodiments, the method of hydrothermally synthesizing cobalt salt, calcium salt, zirconium salt and molybdate into an electrocatalyst precursor comprises:
[0016] Dissolving the cobalt salt, the calcium salt, the zirconium salt and sodium sulfate in water to prepare a first solution;
[0017] Dissolving molybdate in water to prepare a second solution, and adding the second solution dropwise into the first solution under continuous stirring to prepare a mixed solution;
[0018] Acetylene black is added to the mixed solution and dispersed uniformly to obtain a mixed system. After aging the mixed system, the mixed system is subjected to a hydrothermal synthesis reaction. The reaction precipitate is washed with deionized water and vacuum dried to obtain the electrocatalyst precursor.
[0019] In the present disclosure and possible embodiments, the concentration of zirconium salt in the mixed solution is 0.1 to 0.2 mol·L -1 The molar ratio of calcium salt to zirconium salt is in the range of 0.2:0.4 to 1:0.4, the molar ratio of cobalt salt to zirconium salt is in the range of 1:16 to 1:2, and the molar ratio of molybdate to zirconium salt is in the range of 1:40 to 1:5; the concentration of sodium sulfate is 0.05 to 0.1 mol·L -1 ; The mass ratio of acetylene black to sodium sulfate ranges from 0.2:1 to 1:1.
[0020] In the present disclosure and possible embodiments, the aging time is 2 to 10 hours, the hydrothermal synthesis reaction temperature is 90 to 200°C, the hydrothermal synthesis reaction time is 6 to 12 hours, and the vacuum drying temperature is 60 to 80°C.
[0021] In the present disclosure and possible embodiments, the method of calcining the electrocatalyst precursor comprises:
[0022] The calcination treatment is carried out in an air atmosphere at a temperature of 250 to 500° C. for a time of 0.5 to 3 hours. After naturally cooling to room temperature, the desired electrocatalyst is obtained by grinding.
[0023] In the present disclosure and possible embodiments, the calcination temperature is 300° C. and the calcination time is 1 hour.
[0024] In a second aspect, the Ca-doped ZrO2-loaded Co-Mo electrocatalyst is prepared by:
[0025] The product is prepared by the method described in any one of the first aspects.
[0026] In a third aspect, the Ca-doped ZrO2-loaded Co-Mo electrocatalyst described in the second aspect is used in electrocatalytic reduction of nitrogen to synthesize ammonia in an alkaline aqueous electrolyte, and the application method thereof comprises:
[0027] The Ca-doped ZrO2-loaded Co-Mo electrocatalyst was loaded onto carbon felt as the cathode, and pure carbon felt was used as the anode. -1 An electrolytic cell system is composed of an aqueous solution of KOH as an electrolyte, nitrogen is introduced into the electrolytic cell system as a nitrogen source, and direct current electrolysis is performed at room temperature and constant voltage to electrocatalytically reduce nitrogen to synthesize ammonia.
[0028] In the present disclosure and possible embodiments, the flow rate of nitrogen is 200 mL min -1 , the constant voltage is 1.7~2.5V.
[0029] Beneficial effects of the present invention:
[0030] The Ca-doped ZrO2-loaded Co-Mo electrocatalyst disclosed in the present invention regulates the electronic structure of ZrO2 and its loaded Mo component by doping Ca, promotes the activity of nitrogen reduction to produce ammonia, and can significantly inhibit the side reaction of water decomposition and hydrogen, thereby achieving the purpose of improving the selectivity of catalytic ammonia production; in addition, the electrocatalyst preparation process only includes two steps, namely, a hydrothermal reaction and a subsequent calcination treatment, and the preparation process is simple; the hydrothermal reaction solvent is deionized water, and no organic solvent is consumed; and the required salts are added in one step by hydrothermal treatment to synthesize the matrix and load the target Co-Mo bimetallic component, and the process is efficient, simple and controllable, thereby facilitating the rapid and large-scale preparation of the catalyst; the electrocatalyst disclosed in the present invention has a high performance in 1 mol·L -1 The electrocatalytic NRR has good ammonia production activity and high selectivity in KOH alkaline electrolyte: the Faradaic efficiency reaches a maximum of 42.6% at 1.7V and the ammonia production rate reaches a maximum of 59.54μg·h at 2.1V. -1 cm -2 , the Faradaic efficiency can still reach 10.20%, which is significantly better than most known electrocatalysts, thus effectively promoting the development of electrocatalytic NRR ammonia synthesis. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The above and other objects, features and advantages of the present disclosure will become more apparent through the following description of the embodiments of the present disclosure with reference to the accompanying drawings, in which:
[0032] Figure 1 is the XRD spectra of the electrocatalysts of Example 1 and Example 2;
[0033] Figure 2a and 2b They are respectively the SEM image and the local enlarged image of the electrocatalyst of Example 1;
[0034] Figure 3a and 3b They are the TEM image and SAED characterization results of the electrocatalyst of Example 1;
[0035] Figure 4 is the STEM-EDS element distribution map of the electrocatalyst of Example 1;
[0036] Figure 5 is the EDS spectrum of the electrocatalyst of Example 1;
[0037] Figure 6 is the HRTEM characterization result of the electrocatalyst of Example 1;
[0038] Figure 7a-7e They are respectively the Zr 3d, Mo 3d, Co 2p, Ca 2p and O1s XPS fine spectra of the electrocatalyst of Example 1;
[0039] Figure 8a-8c The non-Faraday voltage range cyclic voltammetry curves and double-layer capacitance test results of the electrocatalysts of Example 1 and Example 2 are respectively;
[0040] Fig. 9 It is a comparison of the ammonia production performance of the electrocatalysts prepared in Example 1 and Example 2;
[0041] Fig.10 The ammonia production rate and Faraday efficiency of the electrocatalyst of Example 1 at different electrolysis voltages;
[0042] Fig.11 is the ammonia production performance of the electrocatalysts with different Co / Zr ratios in Example 3;
[0043] Fig.12 is the ammonia production performance of the electrocatalysts with different Mo / Zr ratios in Example 4;
[0044] Fig.13 is the ammonia production stability of the electrocatalyst of Example 5;
[0045] Fig.14 is a comparison of linear voltammetric curves of the electrocatalysts of Comparative Example 1 and Example 1 in an argon-saturated KOH electrolyte;
[0046] Fig.15a and 15b They are respectively the SEM image and the local magnified image of the electrocatalyst prepared in Comparative Example 1;
[0047] Fig.16a and 16b They are the SEM image and local enlarged image of the electrocatalyst prepared in Comparative Example 2. DETAILED DESCRIPTION
[0048] The present disclosure is described below based on embodiments, but it is worth noting that the present disclosure is not limited to these embodiments. In the detailed description of the present disclosure below, some specific details are described in detail. However, for the parts that are not described in detail, those skilled in the art can also fully understand the present disclosure.
[0049] The applicant's research shows that Mo-based electrocatalytic ammonia production activity is high, but unfortunately it also has high catalytic activity for HER; ZrO2 has a stronger bonding adsorption capacity for N2 than for H2, which is beneficial for inhibiting HER, but its adsorption capacity for N2 is too strong, and the activated N2 is difficult to bond with H +Protonation forms NH3, resulting in low electrocatalytic ammonia production activity of ZrO2. The applicant embedded MoS2 and ZrS3 nanocrystals on the ZrO2 nanosheet carrier to form a heterogeneous structure, and developed a MoS2-ZrS3 / ZrO2 electrocatalyst (patent application number 2024113634333), which showed good catalytic performance. However, MoS2 is also an ideal catalyst for hydrogen production by electrolysis of water, with high HER catalytic activity, resulting in the unsatisfactory ammonia production selectivity of MoS2-ZrS3 / ZrO2 electrocatalyst, and there is still much room for improvement.
[0050] To this end, the present invention adopts a two-step hydrothermal synthesis and calcination method to prepare the electrocatalyst, introduces Co to form a Co-Mo bimetallic oxide, synergistically promotes the electrocatalytic activity, and introduces divalent Ca into the matrix ZrO2 2+ , regulating the electronic structure of ZrO2 and its loaded Mo component, regulating the adsorption and activation performance of the electrocatalyst for N2, and at the same time, the divalent Ca 2+ Doped into the ZrO2 lattice, partially replacing tetravalent Zr 4+ In order to maintain local electrical neutrality, the oxygen vacancies on the ZrO2 surface are increased, which is conducive to loosening and activating the N≡N triple bond, further improving the electrocatalytic ammonia production performance of the catalyst.
[0051] Based on the above technical concept, each embodiment of the present disclosure prepares Ca-doped ZrO2-loaded Co-Mo electrocatalyst, which specifically includes the following steps:
[0052] 1. Preparation of electrocatalyst precursor:
[0053] (1) weighing cobalt salt, calcium salt, zirconium salt and structure-directing agent sodium sulfate in a certain proportion, and dissolving the above substances in water to prepare a first solution;
[0054] (2) dissolving a certain amount of molybdate in water to prepare a second solution, and adding the second solution dropwise into the first solution under continuous stirring to prepare a mixed solution;
[0055] (3) adding a certain amount of acetylene black as an auxiliary structure directing agent to the mixed solution, aging the mixed solution at room temperature for a certain period of time after ultrasonic dispersion, and then performing a hydrothermal synthesis reaction at a certain temperature for a certain period of time. After the reaction, the precipitate is washed with deionized water for multiple times, and then vacuum dried to obtain an electrocatalyst precursor.
[0056] In a specific embodiment, the cobalt salt includes cobalt chloride, cobalt sulfate and cobalt nitrate; the calcium salt includes calcium chloride and calcium nitrate; the molybdate includes sodium molybdate and ammonium molybdate; and the zirconium salt includes zirconium oxychloride, zirconium chloride and zirconium nitrate.
[0057] In a specific embodiment, the concentration of zirconium salt in the mixed solution is 0.1-0.2 mol·L -1The molar ratio of calcium salt to zirconium salt is in the range of 0.2:0.4 to 1:0.4; the molar ratio of cobalt salt to zirconium salt is in the range of 1:16 to 1:2; the molar ratio of molybdate to zirconium salt is in the range of 1:40 to 1:5; the concentration of sodium sulfate is 0.05 to 0.1 mol·L -1 ; The mass ratio of acetylene black to sodium sulfate ranges from 0.2:1 to 1:1.
[0058] In a specific embodiment, the aging time ranges from 2 to 10 hours, the hydrothermal synthesis reaction temperature ranges from 90 to 200° C., the hydrothermal synthesis reaction time ranges from 6 to 12 hours, the vacuum drying temperature ranges from 60 to 80° C., and the hydrothermal synthesis reaction is carried out in a hydrothermal reactor with a polytetrafluoroethylene lining.
[0059] 2. The electrocatalyst precursor is placed in a muffle furnace, calcined at a certain temperature for a certain time in an air atmosphere, and then naturally cooled to room temperature and ground to obtain the desired electrocatalyst.
[0060] In a specific embodiment, the calcination temperature ranges from 250 to 500° C., and the calcination time ranges from 0.5 to 3 hours; preferably, the calcination temperature is 300° C., and the calcination time is 1 hour.
[0061] The Ca-doped ZrO2-loaded Co-Mo electrocatalyst of the disclosed embodiment is used in the electrocatalytic reduction of nitrogen to synthesize ammonia in an alkaline aqueous electrolyte, and the specific application method is:
[0062] Ca-doped ZrO2 loaded Co-Mo electrocatalyst was loaded on carbon felt as cathode and pure carbon felt as anode at 0.1 mol·L -1 The electrolytic cell system is composed of KOH aqueous solution as the electrolyte, high-purity nitrogen is introduced into the system as the nitrogen source, and constant voltage direct current electrolysis is performed at normal pressure and room temperature.
[0063] The following are specific embodiments of the present disclosure and corresponding comparative examples, and the beneficial effects of the electrocatalyst of the present invention are illustrated through the performance test data of the embodiments and comparative examples.
[0064] Example 1
[0065] 1. Preparation of electrocatalyst precursor:
[0066] (1) Weighing 6.5 mmol of zirconium oxychloride and 3.5 mmol of sodium sulfate, and then weighing corresponding amounts of calcium chloride and cobalt chloride in a ratio of 0.6:0.4 in the molar ratio of calcium chloride to zirconium oxychloride and 1:4 in the molar ratio of cobalt chloride to zirconium oxychloride, and dissolving the above substances in 30 mL of deionized water to prepare a first solution;
[0067] (2) weighing a corresponding amount of sodium molybdate in a molar ratio of sodium molybdate to zirconium oxychloride of 1:20, and dissolving the sodium molybdate in 20 mL of deionized water to prepare a second solution;
[0068] (3) the second solution was added dropwise to solution A under continuous stirring to prepare a mixed solution, 0.298 g of acetylene black was added to the mixed solution, ultrasonically dispersed for 10 min, aged at room temperature for 8 h, and then hydrothermal synthesis reaction was continued at 180° C. for 8 h. After the reaction, the precipitate was washed with deionized water for multiple times, and vacuum dried to obtain an electrocatalyst precursor;
[0069] 2. The electrocatalyst precursor was placed in a muffle furnace and calcined at 300°C for 1 hour in an air atmosphere. After naturally cooling to room temperature, the resulting mixture was ground to obtain the Ca-doped ZrO2-loaded Co-Mo (Co-Mo / Ca-ZrO2) electrocatalyst of Example 1.
[0070] Example 2
[0071] The preparation method of this embodiment 2 is similar to that of embodiment 1, except that calcium chloride is not added to the prepared first solution, and the remaining steps are the same as those of embodiment 1. The obtained electrocatalyst is Co-Mo / ZrO2.
[0072] Microscopic Characterization and Performance Testing of Electrocatalysts in Examples 1 and 2
[0073] 1. X-ray diffraction (XRD) analysis was performed on the electrocatalysts Co-Mo / Ca-ZrO2 and Co-Mo / ZrO2 of Example 1 and Example 2. The results are shown in Figure 1 .Depend on Figure 1It can be seen that both of them have characteristic diffraction peaks of tetragonal ZrO2 (denoted as t-ZrO2) (PDF: 42-1164) at 2θ = 29.8°, 34.8°, 50.1°, 59.4° and 61.9°, corresponding to their (101), (110), (200), (211) and (202) crystal planes. The diffraction peaks at 2θ = 17.4°, 28.1°, 31.3°, 34.2°, 38.4°, 44.6°, 45.3°, 50.3°, 53.8°, 59.5° and 61.6° are attributed to the (100), (-111), (111), (020), (021), (112), (-202), (-122), (202), (131) and (-213) crystal planes of monoclinic ZrO2 (denoted as m-ZrO2) (PDF: 74-0815). The diffraction peaks at 2θ = 31.3°, 38.5° and 59.3° are attributed to the (220), (222) and (511) crystal planes of Co3O4 (PDF: 78-1969). The diffraction peaks at 2θ = 15.4°, 16.9°, 21.2°, 24.4°, 29.6°, and 33.3° correspond to Mo9O 26 (PDF: 84-1466) (-112), (402), (004), (022), (621) and (206) crystal planes. The difference between the two is that the diffraction peaks of Co-Mo / CaZrO2 at 2θ = 23.1°, 29.8°, 33.0° and 59.6° are attributed to CaO (PDF: 17-0912). Compared with Co-Mo / ZrO2, the diffraction peaks of the t-ZrO2 phase of the Co-Mo / Ca-ZrO2 electrocatalyst after the introduction of Ca are enhanced, indicating that the introduction of Ca further increases the t-ZrO2 phase content of the electrocatalyst.
[0074] 2. The electrocatalyst Co-Mo / Ca-ZrO2 of Example 1 was characterized by scanning electron microscopy (SEM). Figure 2a and Figure 2b It can be seen that, in addition to the acetylene black nanoparticles added during the hydrothermal synthesis distributed on and around the nanosheets, Example 1 successfully synthesized a Co-Mo / Ca-ZrO2 nanosheet electrocatalyst with a diameter of about 400-500 nm and a thickness of about 10-20 nm.
[0075] 3. The catalyst of Example 1 was characterized by transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (EDS). Figure 3a It can be seen that the synthesized Co-Mo / Ca-ZrO2 nanosheets are composed of multiple nanocrystals, and the point-like distribution of selected area electron diffraction (SAED) further indicates that the nanosheets have polycrystalline characteristics ( Figure 3b). High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and EDS of a single nanosheet showed that Zr, Ca, Co, Mo, O, N, and C elements were uniformly distributed on the single electrocatalyst nanosheet, with atomic percentages of 5.45%, 0.15%, 0.05%, 0.10%, 28.23%, 1.23%, and 64.79%, respectively ( Figure 4 af and Figure 5 ). High-resolution transmission electron microscopy (HRTEM) images further confirmed the existence of grains with lattice fringe spacings of 0.288 nm, 0.299 nm, 0.285 nm, and 0.303 nm on the nanosheets, belonging to m-ZrO2, t-ZrO2, Co3O4, and Mo9O, respectively. 26 The (111), (101), (220) and (621) planes ( Figure 6 ai).
[0076] 4. The XPS characterization results of the catalyst of Example 1 are shown in Figure 7a-7e As shown in the Zr 3d fine spectrum of Co-Mo / ZrO2, the Zr 3d at 185.5eV and 187.9eV 5 / 2 and Zr 3d 3 / 2 The two split peaks are attributed to Zr 4+ Zr 3d of Ca-doped Co-Mo / Ca-ZrO2 5 / 2 and Zr 3d 3 / 2 The lower binding energy shifts to 184.7 eV and 187.1 eV, indicating that the doping of Ca element regulates the electronic structure of Zr and electrons transfer to Zr. Similarly, the Mo 3d fine spectra of Co-Mo / ZrO2 and Co-Mo / Ca-ZrO2 electrocatalysts have Mo 3d 5 / 2 and Mo 3d 3 / 2 Two split peaks appear, attributed to Mo 4+ and Mo 6+ , Mo 3d after Ca doping 5 / 2 and Mo3d 3 / 2It also moved to lower binding energy, indicating that Ca doping also caused electrons to transfer to Mo. Due to the low content of the loaded Co component, the Co 2p fine spectra of Co-Mo / ZrO2 and Co-Mo / Ca-ZrO2 electrocatalysts did not show obvious XPS peaks. The Ca 2p fine spectra of the electrocatalysts Co / Ca-ZrO2 and Mo / Ca-ZrO2 loaded with single Co and single Mo did not shift compared with Co-Mo / Ca-ZrO2, indicating that the loading of Co and Mo did not affect the electronic structure of Ca; the three oxygen species peaks Oa, Ob and Oc appeared in the O1s fine spectra of Co-Mo / ZrO2 and Co-Mo / Ca-ZrO2 electrocatalysts without Ca doping, which were attributed to lattice oxygen, oxygen vacancies and adsorbed water molecules, respectively. The undoped Ca Co-Mo / ZrO2 showed characteristic peaks of Oa, Ob and Oc at 532.1eV, 533.3eV and 534.9eV, respectively. After Ca doping, the characteristic peaks of Oa, Ob and Oc moved to 531.4eV, 532.6eV and 534.2eV, respectively, indicating that electrons were transferred to oxygen species including oxygen vacancies, and Ca doping increased the oxygen vacancies of the electrocatalyst, mainly because the divalent Ca 2+ Doping into the ZrO2 lattice partially replaces the tetravalent Zr 4+ In order to maintain local electrical neutrality, the number of oxygen vacancies increases. The electrons captured by oxygen vacancies can be injected into the antibonding orbital of adsorbed N2, which is conducive to loosening and activating the N≡N triple bond.
[0077] 5. The Co-Mo / Ca-ZrO2 and undoped Ca-containing Co-Mo / ZrO2 electrocatalysts prepared in Example 1 and Example 2 were subjected to 0.1 mol L -1 Electrochemically active area (ECSA) was measured in KOH using an electrochemical workstation with a non-Faraday voltage range of 1.025 to 1.125 V at 40 mV·s -1 , 50mV·s -1 、60mV·s -1 、70mV·s -1 and 80mV·s -1 Cyclic voltammetry (CV) scans were performed at a scan rate of Figure 8a and Figure 8b ), with the scan rate as the horizontal axis and the current density difference (Δj) between the anode branch and the cathode branch corresponding to the middle value 1.075V in the range of 1.025 to 1.125V as the vertical axis ( Figure 8c ), and then linear regression is performed to obtain the slope of the straight line. 1 / 2 of the slope value is the measured double layer capacitance (C dl ), according to C dlThe value is proportional to the ECSA, which is used to evaluate the ECSA of Co-Mo / ZrO2 and Co-Mo / Ca-ZrO2. Figure 8c It can be seen that the C of Co-Mo / ZrO2 and Co-Mo / Ca-ZrO2 dl 8.35mF·cm -2 and 10.0mF·cm -2 , indicating that Ca-doped Co-Mo / Ca-ZrO2 has a larger ECSA. The electrocatalysts prepared in Example 1 and Example 2 were subjected to 0.1 mol·L nitrogen saturated -1 The ammonia production performance of the samples was compared in KOH electrolyte at 2.1V constant voltage for 2h. Fig. 9 ), compared with the undoped Ca-Co-Mo / ZrO2, the ammonia production rate and Faraday efficiency of the Ca-doped Co-Mo / Ca-ZrO2 were significantly improved.
[0078] 6. The Co-Mo / Ca-ZrO2 electrocatalyst prepared in Example 1 was subjected to a nitrogen-saturated 0.1 mol·L -1 The electrolysis voltage was optimized by constant voltage electrolysis for 2 h in KOH electrolyte at different voltages (1.5-2.5 V). Fig.10 It can be seen that at 1.7V, the ammonia production rate is 37.11μg·h -1 cm -2 The Faraday efficiency reached a maximum of 42.6% and the ammonia production rate reached a maximum of 59.54 μg·h at 2.1 V. -1 cm -2 , and the Faraday efficiency is 10.20%, indicating that the electrocatalyst not only has a high catalytic activity for ammonia production, but also has a relatively ideal ammonia production selectivity.
[0079] Compared with the MoS2-ZrS3 / ZrO2 electrocatalyst disclosed in the patent application No. 2024113634333 described in the background technology, the Faraday efficiency at 1.7V is greatly improved from 15.97% to 42.6%, and the ammonia production rate is increased from 16.89μg·h -1 cm -2 Increased to 37.11 μg·h -1 cm -2 At 2.1 V, the Faraday efficiency increased from 8.94% to 10.20%, and the ammonia production rate was 54.99 μg·h -1 cm -2 Increased to 59.54 μg·h -1 cm -2 .
[0080] The above comparative data show that the Co-Mo / Ca-ZrO2 prepared by the technical solution provided in Example 1 significantly improves the selectivity of electrocatalytic ammonia production, and its catalytic ammonia production activity is also improved.
[0081] Example 3
[0082] This Example 3 is similar to Example 1, except that: in this Example, the molar ratio of cobalt chloride and zirconium oxychloride (Co / Zr ratio) is changed to 0, 1:16, 1:8, 1:4 and 1:2, respectively, and the Co / Zr ratio is optimized. The remaining steps are the same as in Example 1.
[0083] The electrocatalyst obtained in Example 3 was subjected to nitrogen saturation at 0.1 mol·L -1 The ammonia production performance in KOH electrolyte was evaluated and the results are shown in Fig.11 ,Depend on Fig.11 It can be seen that as the Co / Zr ratio increases, the ammonia production rate and the Faraday efficiency first decrease, and then increase with the increase of the Co / Zr ratio. When the Co / Zr ratio is 1:4, they reach the highest value and then decrease.
[0084] Example 4
[0085] This Example 4 is similar to Example 1, except that: in this Example, the molar ratio of sodium molybdate and zirconium oxychloride (Mo / Zr ratio) is changed to 0, 1:20, 1:10 and 1:5 respectively, the Mo / Zr ratio is optimized, and the remaining steps are the same as in Example 1.
[0086] The electrocatalyst obtained in Example 4 was subjected to nitrogen saturation at 0.1 mol·L -1 The ammonia production performance in KOH electrolyte was evaluated and the results are shown in Fig.12 ,Depend on Fig.12 It can be seen that the ammonia production rate and the Faradaic efficiency increase with the increase of the Mo / Zr ratio, reaching the maximum value when the Mo / Zr ratio is 1:20, and then decrease.
[0087] Example 5
[0088] The Co-Mo / Ca-ZrO2 electrocatalyst prepared in Example 1 was subjected to a nitrogen-saturated 0.1 mol·L -1 The stability test of electrocatalytic ammonia production was carried out in KOH electrolyte. The electrolysis was performed for 2 h as one cycle. The results are shown in Fig.13 As shown by Fig.13 It can be seen that the ammonia production rate and Faraday efficiency of the Co-Mo / Ca-ZrO2 electrocatalyst decreased with the increase of electrolysis times in the first three electrolysis cycles, and then the catalytic ammonia production performance tended to be stable. The ammonia production rate and Faraday efficiency of the eighth cycle were maintained at 48.34 μg·h -1cm -2 and 9.14%, indicating that the electrocatalyst has good catalytic stability for ammonia production.
[0089] Comparative Example 1
[0090] Based on Example 1, Co-Mo / CaO without adding zirconium salt was further prepared, which was different from Example 1 in that zirconium oxychloride was not added in the hydrothermal reaction, and the rest of the steps were the same as Example 1. It was compared with the Co-Mo / Ca-ZrO2 electrocatalyst prepared in Example 1 to examine the inhibitory effect of adding Zr on HER.
[0091] The electrocatalysts Co-Mo / Ca-ZrO2 prepared in Example 1 and Co-Mo / CaO prepared in the comparative example were heated to 0.1 mol·L in an argon-saturated atmosphere. -1 In KOH electrolyte, the -1 A linear voltammetric scan was performed at a rate of Fig.14 As shown. The reduction current obtained by linear voltammetric scanning in an argon-saturated electrolyte is attributed to the occurrence of HER on the electrocatalyst surface. The reduction current of the Co-Mo / Ca-ZrO2 electrocatalyst with added zirconium salt is significantly lower than that of Co-Mo / CaO without added zirconium salt, indicating that the Co-Mo / Ca-ZrO2 electrocatalyst prepared by adding zirconium salt has a significant HER inhibition effect.
[0092] Comparative Example 2
[0093] Based on Example 1, Co-Mo / Ca-ZrO2 is further prepared without adding sodium sulfate and acetylene black. The difference from Example 1 is that sodium sulfate and acetylene black are not added during the hydrothermal reaction, and the remaining steps are the same as Example 1.
[0094] Comparative Example 3
[0095] On the basis of Example 1, Co-Mo / Ca-ZrO2 was further prepared by adding sodium sulfate but not adding acetylene black. The difference from Example 1 is that acetylene black was not added during the hydrothermal reaction, and the remaining steps were the same as Example 1.
[0096] The SEM characterization results of the electrocatalysts prepared in Comparative Example 2 and Comparative Example 3 are shown in Fig.15a , 15b , 16a and Fig.16b ,Depend on Fig.15a , 15b It can be seen that the electrocatalyst prepared in Comparative Example 2 without adding sodium sulfate and acetylene black is dispersed nanoparticles. Fig.16a , 16bIt can be seen that the electrocatalyst prepared in Comparative Example 3 with the addition of sodium sulfate but without the addition of acetylene black has two morphologies. One is that smaller nanoparticles are aggregated into larger jujube-like nanoparticles, and a large number of nanosheets are generated. Comparative Example 3 is compared with Comparative Example 2, indicating that the addition of sodium sulfate has a directing agent effect on the hydrothermal synthesis of nanosheet Co-Mo / Ca-ZrO2 electrocatalyst. Example 1 is to add acetylene black on the basis of the addition of sodium sulfate in Comparative Example 3. The SEM image of the prepared electrocatalyst ( Figure 2a , 2b ) It can be seen that except for the added acetylene black nanoparticles, almost all of them are Co-Mo / Ca-ZrO2 nanosheets, indicating that after adding acetylene black, the jujube-like nanoparticles formed in Comparative Example 3 almost disappeared, further indicating that acetylene black has the function of an auxiliary directing agent.
[0097] The above-described embodiments are only embodiments of the present disclosure, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the present disclosure. It should be noted that, for a person of ordinary skill in the art, without departing from the concept of the present disclosure, several variations, equivalent substitutions, improvements, etc. may be made, all of which fall within the scope of protection of the present disclosure. Therefore, the scope of protection of the present disclosure shall be subject to the attached claims.
Claims
1. A method for preparing a Ca-doped ZrO2-loaded Co-Mo electrocatalyst, characterized in that: include: Hydrothermally synthesizing cobalt salt, calcium salt, zirconium salt and molybdate to prepare electrocatalyst precursor; The electrocatalyst precursor is calcined to obtain the Ca-doped ZrO2-loaded Co-Mo electrocatalyst.
2. The method for preparing an electrocatalyst according to claim 1, characterized in that: The cobalt salts include cobalt chloride, cobalt sulfate and cobalt nitrate; The calcium salts include calcium chloride and calcium nitrate; The molybdate includes sodium molybdate and ammonium molybdate; The zirconium salts include zirconium oxychloride, zirconium chloride and zirconium nitrate.
3. The method for preparing an electrocatalyst according to claim 2, characterized in that: The method of hydrothermally synthesizing a cobalt salt, a calcium salt, a zirconium salt and a molybdate into an electrocatalyst precursor comprises: Dissolving the cobalt salt, the calcium salt, the zirconium salt and sodium sulfate in water to prepare a first solution; Dissolving molybdate in water to prepare a second solution, and adding the second solution dropwise into the first solution under continuous stirring to prepare a mixed solution; Acetylene black is added to the mixed solution and dispersed uniformly to obtain a mixed system. After aging the mixed system, the mixed system is subjected to a hydrothermal synthesis reaction. The reaction precipitate is washed with deionized water and vacuum dried to obtain the electrocatalyst precursor.
4. The method for preparing an electrocatalyst according to claim 3, characterized in that: The concentration of zirconium salt in the mixed solution is 0.1-0.2 mol·L -1 The molar ratio of calcium salt to zirconium salt is in the range of 0.2:0.4 to 1:0.4, the molar ratio of cobalt salt to zirconium salt is in the range of 1:16 to 1:2, and the molar ratio of molybdate to zirconium salt is in the range of 1:40 to 1:5; the concentration of sodium sulfate is 0.05 to 0.1 mol·L -1 ; The mass ratio of acetylene black to sodium sulfate ranges from 0.2:1 to 1:
1.
5. The method for preparing an electrocatalyst according to claim 3 or 4, characterized in that: The aging time is 2 to 10 hours, the hydrothermal synthesis reaction temperature is 90 to 200° C., the hydrothermal synthesis reaction time is 6 to 12 hours, and the vacuum drying temperature is 60 to 80° C.
6. The method for preparing an electrocatalyst according to claim 5, characterized in that: The method of calcining the electrocatalyst precursor comprises: The calcination treatment is carried out in an air atmosphere at a temperature of 250 to 500° C. for a time of 0.5 to 3 hours. After naturally cooling to room temperature, the desired electrocatalyst is obtained by grinding.
7. The method for preparing an electrocatalyst according to claim 5, characterized in that: The calcination temperature is 300° C. and the calcination time is 1 hour.
8. A Ca-doped ZrO2-loaded Co-Mo electrocatalyst, characterized in that: The preparation method of the electrocatalyst is: The method is prepared by any one of claims 1 to 7.
9. The electrocatalyst of claim 9 is used in the electrocatalytic reduction of nitrogen to synthesize ammonia in an alkaline aqueous electrolyte, characterized in that: The method of application includes: The electrocatalyst was loaded onto carbon felt as the cathode, and pure carbon felt was used as the anode. -1 An electrolytic cell system is composed of an aqueous solution of KOH as an electrolyte, nitrogen is introduced into the electrolytic cell system as a nitrogen source, and direct current electrolysis is performed at room temperature and constant voltage to electrocatalytically reduce nitrogen to synthesize ammonia.
10. The use according to claim 9, characterized in that: The nitrogen flow rate is 200 mL min -1 , the constant voltage is 1.7~2.5V.